Risk factors for and impact of poststroke pneumonia in patients with acute ischemic stroke. Issue 12 (26th March 2021) - Yuan, Minghao; Li, Qi; Zhang, Rongrong; Zhang, Wenyu; Zou, Ning; Qin, Xinyue; Cai, Zhiyou
Abstract : Abstract: Poststroke pneumonia (PSP) is a common complication of stroke and an important cause of death following stroke. However, the treatment of PSP remains inadequate due to severe impairment to the respiratory system by PSP. Thus, it is crucial to focus on preventing PSP to improve the prognosis of patients with stroke. This prospective single-center Cohort study aimed to investigate the risk factors for pulmonary infection following an ischemic stroke and identify whether PSP significantly influences the prognosis of patients after stroke. Altogether, 451 patients who were treated for acute ischemic stroke in the First Affiliated Hospital of Chongqing Medical University in China between April 2017 and April 2018 were enrolled. Clinical data from the patients from admission to 3 months after discharge were collected. PSP was the primary outcome and poor prognosis or death at 3 months following discharge was the secondary outcome observed in this study. We performed logistic regression analyses to identify the risk factors for PSP and test an association between pneumonia and poor prognosis or death after stroke. Our findings revealed the following risk factors for PSP: atrial fibrillation odds ratio (OR) = 2.884, 95% confidence intervals (CI) = 1.316–6.322), being bedridden (OR = 2.797, 95%CI = 1.322–5.921), subject to an invasive procedure (OR = 12.838, 95%CI = 6.296–26.178), massive cerebral infarction (OR = 3.994, 95%CI = 1.496–10.666), and dysphagia (OR = 2.441, 95%CI = 1.114–5.351). Pneumonia was a risk factor for poor prognosis (OR = 2.967, 95%CI = 1.273–6.915) and death (OR = 5.493, 95%CI = 1.825–16.53) after stroke. Hence, since pneumonia increases the risk of poor prognosis and death following acute ischemic stroke, preventing, and managing the risk factors for PSP may improve the prognosis and reduce the mortality after stroke.